Conservative management of Jones fractures with immediate weight-bearing in a walking boot demonstrates healing. (March 2022) - Look, Nicole; Reisenauer, Colin R.; Gorman, Melissa A.
Highlights: Treatment of acute Jones fractures without weight-bearing restrictions in a walking boot leads to satisfactory results. Three of 47 patients treated in this case series failed non-operative management and required surgical intervention. Our results demonstrate a decreased need for prolonged immobilization and weight bearing restrictions. Conclusions are limited to an adult population not involved in competitive athletics. Abstract: Jones fractures, or proximal metatarsal fractures at the level of the fourth and fifth intermetatarsal junction, have a high risk for nonunion due to a vascular watershed region. Classically, treatment consists of weight bearing restrictions in a cast or surgical fixation. Some studies have assessed immediate weight bearing following a Jones fracture. Due to conflicting results, the most appropriate treatment method remains unclear. This study analyzes outcomes after treating adults with acute Jones fractures non-operatively without weight bearing restrictions in a walking boot. This study hypothesizes that patients will not require future operative intervention following functional treatment. A retrospective review of 55 adult patients who sustained acute, closed Jones fractures was conducted. 47 were treated weight bearing as tolerated (WBAT) in a walking boot and eight were treated non-weight bearing (NWB) in a cast. They were followed radiographically by an orthopedic surgeon for an average of 6.4 and 15.5 months, respectively. Three patients in each group (6.4% WBAT, 37.5% NWB) developed painful nonunion leading to surgical fixation. Thirty (66.7%) patients in the WBAT group demonstrated radiographic union on final radiographs. Only two (13.3%) of the 15 patients with partial union were seen at least six months from time of injury, one of whom had ongoing pain but declined surgery. The remaining 13 patients were asymptomatic at their final clinic appointment. Controversy still exists as to the best treatment methodology for acute Jones fractures. Due to a lack of clear guidelines, it can be difficult for the multiple medical specialties involved to evaluate and treat this injury. Our study suggests that non-operative management of minimally displaced Jones fractures, in the adult, low demand population, without weight bearing restrictions in a walking boot offers similar outcomes to cast immobilization with weight bearing restrictions, resulting in bony union or asymptomatic fibrous nonunion.